The Relationship Between Employee Behavior and Compliance With COVID-19 Self-Assessment Health Protocols at PT. Summarecon Serpong Tangerang - Mulyadi, Matthew Adriel (International Journal Labs, 2025)
In Indonesia, the COVID-19 pandemic infected over six million people, causing more than one hundred and fifty thousand deaths. To prevent the spread, companies implemented health protocols, including mandatory COVID-19 risk self-assessments for employees. Summarecon Serpong Company requires employees to complete this self-assessment. This study aimed to examine the relationship between employee behavior—responsibility, discipline, and honesty—and compliance in completing the COVID-19 self-assessment at Summarecon Serpong. The research used correlation analysis with data collected via a questionnaire. The questionnaire employed a Likert scale to measure respondents’ attitudes and perceptions and contained 20 questions, divided equally among responsibility, discipline, honesty, and compliance. A total of 63 respondents participated. Data were analyzed using validity and reliability tests, followed by Spearman Rank Correlation to determine relationships. Results showed a high and significant correlation between all three behavioral components and compliance. The Spearman correlation coefficients (r) for responsibility, discipline, and honesty were all above 0.7. Additionally, cross-tabulation analysis found a statistically significant link between good behavior and adherence (p < 0.001, OR 5.8; 95% CI 2.592–13.036). These findings indicate a very strong, positive, and statistically significant correlation between employee behavior and compliance with COVID-19 self-assessment protocols at PT. Summarecon Serpong Tangerang.